Demokrasi dalam Perspektif Islam - Vandita, Lalu Yoga; Saputra, Hirmayadi (LPPM Institut Pendidikan Nusantara Global, 2024)
Islam is a universal religion containing the principles of human rights as a teaching concept. Islam positions humans on an equal footing with other humans. This is based on several things. First, Islam is a religion of law with the understanding that Islam applies to everyone regardless of class, the social structure of society from the upper class to the lower class, from the bourgeoisie to the proletariat, all are treated equally before the law. Democracy is a concept of a political system, even before, it has been agreed that Islamic teachings contain democratic principles. Democracy itself can take the form of institutions and value systems. The principle of humanity is beyond primordial boundaries and interests. This is the principle adopted by the Indonesian State which is based on Pancasila with the principle of Bhinneka Tunggal Ika